Transplantation of a myelodysplastic syndrome by a long-term repopulating hematopoietic cell - Chung, Yang Jo (National Academy of Sciences, 2008)
The myelodysplastic syndromes (MDS) comprise a group of premalignant hematologic disorders characterized by ineffective hematopoiesis, dysplasia, and transformation to acute myeloid leukemia (AML). Although it is well established that many malignancies can be transplanted, there is little evidence to demonstrate that a premalignant disease entity, such as MDS or colonic polyps, can be transplanted and subsequently undergo malignant transformation in vivo. Using mice that express a NUP98-HOXD13 (NHD13) transgene in hematopoietic tissues, we show that a MDS can be transplanted to WT recipients. Recipients of the MDS bone marrow displayed all of the critical features of MDS, including peripheral blood cytopenias, dysplasia, and transformation to AML. Even when transplanted with a 10-fold excess of WT cells, the NHD13 cells outcompeted the WT cells over a 38-week period. Limiting-dilution experiments demonstrated that the frequency of the cell that could transmit the disease was ≈1/6,000–1/16,000 and that the MDS was also transferable to secondary recipients as a premalignant condition. Transformation to AML in primary transplant recipients was generally delayed (46–49 weeks after transplant); however, 6 of 10 secondary transplant recipients developed AML. These findings demonstrate that MDS originates in a transplantable, premalignant, long-term repopulating, MDS-initiating cell.